Knowledge, attitude and tuberculosis infection control practice among healthcare workers in DOTS centres in Lagos, Nigeria - Ekuma, Agantem Emmanuel; Oridota, Ezekiel Sofela (International Journal of Infection Control, 2016)
Tuberculosis (TB) is highly transmissible in resource-limited healthcare facilities and healthcare workers (HCWs) are at increased risk for acquiring TB in such settings. Training of healthcare workers in the different areas of TB control program including TB infection control (IC) has been identified as an important factor in increasing the success of TB control since they are responsible for the implementation of IC measures in healthcare settings. The aim of this study was to assess the knowledge, attitude and practice of infection control among healthcare workers in DOTS centers in Lagos State, Nigeria. This was a questionnaire based, cross sectional study involving 182 healthcare workers in 9 DOTS centers in Lagos State including an assessment of the presence of administrative control measures for TB IC in 9 DOTS centers. Questionnaires were completed by 182 participants and nine DOTS centers were surveyed for administrative measures for TB infection control. While most of the questions were correctly answered by most participants, only 64.3% of respondents were able to correctly differentiate between pictures of N95 mask and face mask. Attitudes were mostly in compliance to TB infection control guidelines and majority of respondents reported always carrying out all of the five TB infection control activities surveyed but not all respondents knew their HIV status. Two centers did not have a documented TB infection control policy document but all had adequate ventilation in the TB patients’ waiting area. There are significant gaps in knowledge on TB infection control among healthcare workers in DOTS centers and practice of TB infection control in DOTS centers in Lagos state is not fully compliant with national guidelines.